1994
DOI: 10.1111/j.1439-0507.1994.tb00789.x
|View full text |Cite
|
Sign up to set email alerts
|

A miconazole lacquer in the treatment of Candida‐associated denture stomatitis

Abstract: Summary. An open randomized controlled study involving two parallel treatment groups comprising 50 patients with Candida‐associated denture stomatitis was performed to evaluate the efficacy and safety of one application of 1 g of miconazole 55 mg/g denture lacquer in comparison with that of a commercially available miconazole 2% gel applied four times daily for 2 weeks. The results showed a pronounced reduction in the yeast scores and a reduction in the palatal erythema in both treatment groups, but there was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 11 publications
(1 reference statement)
0
21
0
1
Order By: Relevance
“…Despite this limitation, the results found in the present study showed that all the products used presented efficacy for denture stomatitis clinical cure or reduction and for number of Candida albicans colonies in culture elimination or reduction. Few double-blinded, controlled-randomized clinical-trials studies for topical treatment comparison of Candida -associated denture stomatitis between Brazilian green propolis and current medicinal treatment generally done with topical well-known antifungal as miconazole gel [2, 5] have been reported. According to our best knowledge, this is the first study which reports the use of 2.5% propylene glycol extract of Brazilian green propolis for the treatment of Candida -associated denture stomatitis, comparing clinical erythema and count of CFUs before and after treatment and that established the best safety Brazilian green propolis concentration through Candida inhibition test and that made Candida spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite this limitation, the results found in the present study showed that all the products used presented efficacy for denture stomatitis clinical cure or reduction and for number of Candida albicans colonies in culture elimination or reduction. Few double-blinded, controlled-randomized clinical-trials studies for topical treatment comparison of Candida -associated denture stomatitis between Brazilian green propolis and current medicinal treatment generally done with topical well-known antifungal as miconazole gel [2, 5] have been reported. According to our best knowledge, this is the first study which reports the use of 2.5% propylene glycol extract of Brazilian green propolis for the treatment of Candida -associated denture stomatitis, comparing clinical erythema and count of CFUs before and after treatment and that established the best safety Brazilian green propolis concentration through Candida inhibition test and that made Candida spp.…”
Section: Discussionmentioning
confidence: 99%
“…This etiology is multifactorial involving predisposing factors, for example, denture stability, oral and denture hygiene, lasting use, systemic factors like immunologic and endocrinal diseases, nutritional deficiency, and some medications including corticoids, antibiotics, and immunossupressors [3, 4]. An association between denture stomatitis and Candida spp., specially Candida albicans, has been reported [2, 57]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main etiologic factors related to denture stomatitis are trauma, poor oral hygiene and infection with Candida species [4,14,17]. Patients often complain of pain and edema in the inflamed areas [3,18]. Chronic inflammation in the area may lead to an increase in bone resorption beneath the denture [20].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, clinicians usually prescribe antifungals along with oral hygiene instructions and prosthesis adjustments [3234]. However, a high recurrence rate and recolonization by Candida after cessation of antifungal therapy are widely reported [3537].…”
Section: Introductionmentioning
confidence: 99%